THE DEVELOPMENT OF A PLAYGROUND AS AN EFFORT TO REDUCE THE IMPACT OF SMARTPHONE USE ON CHILD'S MINDSET - Vera Rimbawani Sushanty; Ananda Liony Putra (Community Service Journal of Indonesia, 2021)
Children in this millennial era cannot be separated from the use of smartphones, of course, without parental supervision, it will have an impact on the development of children's mental and psychological conditions. Excessive use of gadgets causes children to do little or even no physical activity at all, such as playing with their friends. Whereas physical activity in children affects the growth and development of children. Therefore, at the Bhayangkara University Surabaya Real Work Lecture, group 062 students took the initiative to make a playground in Tebel Village, Gedangan District, Sidoarjo Regency on 22 May - 6 June 2021. The children and residents around the play area were very happy and excited to come and take advantage of these facilities. It is expected that children are more active and can socialize with their peers.